Poverty and Inequality Dynamics: Measuring Dampening and IGTI in Three CAFTA-DR Countries - Vanegas, Manuel; Roe, Terry (Journal of Developing Economies, 2024)
This article examines the relationships between extreme poverty, economic growth, and inequality, assesses if changes in inequality dampen the impact of income on extreme poverty, and determines the magnitude of the inequality growth trade-off index in Costa Rica, the Dominican Republic, and Honduras. A country-specific ARDL bound regression was conducted. The findings indicate the presence of direct and indirect dampening impacts of changes in inequality on income growth and extreme poverty reduction. The magnitude of the inequality growth trade-off- index indicates whether to prioritize growth and/or inequality reducing policies. This means that the higher the inequality, as in Honduras, the higher the economic or average income growth rate required to compensate for the increase in inequality to achieve a given level of extreme poverty reduction. Accordingly, there is no one-size-fits-all policy approach to tackling extreme poverty.